The average effective dose of 4-amino-5-(furan-2-yl)-4H-1 ,2,4-triazole-3-thiol in experimental hepatitis - I. M. Belay; E. O. Mihayluk; V. V. Parchenko; O. I. Panasenko; E. G. Knysh (Zaporožskij Medicinskij Žurnal)
The work presents the research of the average effective dose of 4-amino-5-(furan-2-yl)-4H-1,2,4-triazole-3-thiol in experimental hepatitis. Recalculations conducted for the human with the sensitivity coefficient, average effective dose for human is 13,87 mg/kg.